Practices of Interethnic Interaction and Formation of the National and Civic Identity in the South of Russia - Grigorievich Volkov, Yury; Sergeevna Denisova, Galina; Vladimirovich Lubsky, Anatoly; Petrovna Voytenko, Valeria (International Journal of Engineering and Technology, 2018)
The article deals with institutional formal and informal practices of interethnic cooperation and their influence on developing the national and civic identity in polyethnic communities in the South of Russia. The doctrinal documents and statutory regulations that govern the formal practices of interethnic cooperation contemplate involving civil society institutions in implementing the state national policy of the Russian Federation within the framework of the public-private partnership, thus creating institutional conditions for developing the national and civic identity. Informal practices of interethnic cooperation that have formed in local communities as a result of the dialogue between government officials, nongovernmental organizations, and ethnic groups allow developing common goals and public values, which are the basis of developing the national and civic identity and strengthening the civil unity.Â Â